Mindful Parenting as a Strategy to Reduce Parenting Stress in Parents with Early Childhood - Rayani, Siti (Jujurnal Publisher, 2024)
Parenting stress is a common challenge experienced by parents of young children, often leading to negative emotional and behavioral consequences. Mindful parenting has emerged as an effective strategy to reduce parenting stress by fostering awareness, emotional regulation, and responsive interactions between parents and children. This study employs a qualitative approach through a literature review (library research) to explore the role of mindful parenting in alleviating stress among parents with young children. By analyzing existing theoretical frameworks and empirical findings, this research highlights how mindfulness-based practices enhance parental well-being and improve parent-child relationships. Key components of mindful parenting, such as present-moment awareness, nonjudgmental acceptance, self-compassion, and emotional responsiveness, are discussed in relation to their impact on stress reduction. Findings indicate that mindful parenting contributes to lower levels of stress, increased emotional resilience, and greater parental satisfaction. Furthermore, the literature suggests that mindfulness interventions, such as meditation, breathing exercises, and structured programs, can effectively enhance mindful parenting skills. This study underscores the importance of integrating mindful parenting practices into family life and parenting programs to promote healthier parent-child interactions. The results provide valuable insights for psychologists, educators, and policymakers in developing strategies to support parents in managing stress effectively. Future research should explore the practical application of mindful parenting in diverse family contexts to ensure broader applicability.